THE EFFECTIVENESS OF MODERN DRESSINGS ON CHRONIC WOUND HEALING: A LITERATURE REVIEW - Talib, Eka; Maane, Marwan Sulistiawan; Riman, Riman; Sulasti, Devi; Anastazya, Ade Masayu Dwi; Islaeli, Islaeli (Nursing Genius Journal, 2025)
Background: Chronic wounds, such as diabetic foot ulcers, are a serious health problem with increasing prevalence and risk of complications like infection and amputation. Modern wound dressing, as an innovative approach, is considered effective in creating an optimal moist wound environment to accelerate healing. Purpose: This literature review aims to analyze the effectiveness of various types of modern dressings on the chronic wound healing process. Methods: Articles were collected from PubMed, Google Scholar, and ScienceDirect databases using the keywords "Modern wound dressing" AND ("hydrocolloid" OR "alginate" OR "silver dressing") AND "chronic wound healing", limited to publications from 2021 to 2025. A total of 10 articles met the inclusion criteria. Results: The findings indicate that modern dressings (hydrocolloid, silver dressing, alginate) are effective in accelerating wound healing through mechanisms such as maintaining a moist environment, enhancing angiogenesis and collagen deposition, modulating immune responses (M2 macrophage polarization), and providing an antibacterial effect. Conclusion:  These dressings are relatively safe, biocompatible, and can improve patient comfort. However, their effectiveness depends greatly on the accurate selection of the dressing type according to wound characteristics. Training for healthcare workers in dressing selection and further research on the development of innovative materials, such as bioactiveloaded dressings, are recommended.